Pediatric patients with COVID-19 admitted to intensive care units in Brazil: a prospective multicenter study - Arnaldo Prata-Barbosa; Fernanda Lima-Setta; Gustavo Rodrigues dos Santos; Vanessa Soares Lanziotti; Roberta Esteves Vieira de Castro; Daniela Carla de Souza; Carlos Eduardo Raymundo; Felipe Rezende Caino de Oliveira; Lucio Flavio Peixoto de Lima; Cristian Tedesco Tonial; José Colleti, Jr; Ana Paula Novaes Bellinat; et al. (Elsevier, 2020)
Objective: To describe the clinical characteristics of children and adolescents admitted to intensive care with confirmed COVID-19. Method: Prospective, multicenter, observational study, in 19 pediatric intensive care units. Patients aged 1 month to 19 years admitted consecutively (March-May 2020) were included. Demographic, clinical-epidemiological features, treatment, and outcomes were collected. Subgroups were compared according to comorbidities, age < 1 year, and need for invasive mechanical ventilation. A multivariable logistic regression model was used for predictors of severity. Results: Seventy-nine patients were included (ten with multisystemic inflammatory syndrome). Median age 4 years; 54% male (multisystemic inflammatory syndrome, 80%); 41% had comorbidities (multisystemic inflammatory syndrome, 20%). Fever (76%), cough (51%), and tachypnea (50%) were common in both groups. Severe symptoms, gastrointestinal symptoms, and higher inflammatory markers were more frequent in multisystemic inflammatory syndrome. Interstitial lung infiltrates were common in both groups, but pleural effusion was more prevalent in the multisystemic inflammatory syndrome group (43% vs. 14%). Invasive mechanical ventilation was used in 18% (median 7.5 days); antibiotics, oseltamivir, and corticosteroids were used in 76%, 43%, and 23%, respectively, but not hydroxychloroquine. The median pediatric intensive care unit length-of-stay was five days; there were two deaths (3%) in the non- multisystemic inflammatory syndrome group. Patients with comorbidities were older and comorbidities were independently associated with the need for invasive mechanical ventilation (OR 5.5; 95% CI, 1.43-21.12; p = 0.01). Conclusions: In Brazilian pediatric intensive care units, COVID-19 had low mortality, age less than 1 year was not associated with a worse prognosis, and patients with multisystemic inflammatory syndrome had more severe symptoms, higher inflammatory biomarkers, and a greater predominance of males, but only comorbidities and chronic diseases were independent predictors of severity. Resumo: Objetivo: Descrever as características clínicas de crianças e adolescentes internados em unidade de terapia intensiva com COVID-19 confirmada. Método: Estudo prospectivo, multicêntrico, observacional, em 19 unidades de terapia intensiva pediátrica. Foram incluídos pacientes entre um mês e 19 anos, admitidos consecutivamente (março a maio de 2020). As características demográficas, clínico-epidemiológicas, o tratamento e os resultados foram coletados. Os subgrupos foram comparados de acordo com as comorbidades, idade <1 ano e necessidade de ventilação mecânica invasiva. Um modelo de regressão logística multivariável foi utilizado para preditores de gravidade. Resultados: Setenta e nove pacientes foram incluídos (10 com síndrome inflamatória multissistêmica). Mediana de idade, quatro anos; 54% eram do sexo masculino (síndrome inflamatória multissistêmica, 80%); 41% tinham comorbidades (síndrome inflamatória multissistêmica, 20%). Febre (76%), tosse (51%) e taquipneia (50%) foram comuns nos dois grupos. Sintomas graves e gastrointestinais e marcadores inflamatórios mais elevados foram mais frequentes na presença de síndrome inflamatória multissistêmica. Infiltrados intersticiais pulmonares foram comuns em ambos os grupos, mas o derrame pleural foi mais prevalente no grupo com síndrome inflamatória multissistêmica (43% vs. 14%). A ventilação mecânica invasiva foi utilizada em 18% (mediana 7,5 dias); antibióticos, oseltamivir e corticosteroides foram utilizados em 76%, 43% e 23%, respectivamente, mas não a hidroxicloroquina. A mediana do tempo de permanência na unidade de terapia intensiva pediátrica foi de 5 dias; duas mortes ocorreram (3%) no grupo não- síndrome inflamatória multissistêmica. Os pacientes com comorbidades eram mais velhos, e as comorbidades foram independentemente associadas à necessidade de ventilação mecânica invasiva (OR 5,5; IC95%, 1,43-21,12; P 0,01). Conclusões: Nas unidades de terapia intensiva pediátrica brasileiras, a COVID-19 apresentou baixa mortalidade, a idade inferior a um ano não foi associada a um pior prognóstico, os pacientes com síndrome inflamatória multissistêmica apresentaram sintomas mais graves, biomarcadores inflamatórios mais elevados e uma grande predominância no sexo masculino, mas apenas a presença de comorbidades e doenças crônicas foi um preditor independente de gravidade.